Microalga-Based Electricity Production: A Comprehensive Review - Wid Alrashidi; Safiah Alhazmi; Fotoon Sayegh; Sherif Edris (Energies, 2025)
This review evaluates the feasibility of using microalgal culture for sustainable energy production, emphasizing microbial fuel cells (MFCs) and biophotovoltaics (BPVs). This study’s uniqueness is rooted in its thorough examination of recent developments (2014–present) in microalgal strain selection, bioreactor design, and electrode materials. Furthermore, this review combines microalga cultivation with wastewater treatment, highlighting its importance. Notably, it examines advanced methodologies, such as the use of genetic engineering to enhance microalgal traits, nanotechnology to optimize electrode efficacy, and artificial intelligence (AI) to optimize bioelectrochemical systems. In addition, this study identifies possible future research avenues by examining microalga–bacterium consortia and cascaded biobattery systems. Consequently, the incorporation of case studies illustrating microalga biobatteries’ practical applications in low-power devices and wastewater treatment underscores the technology’s promise. Similarly, this study examines significant problems with enhancing farming methods, reconciling cost and yield, and integrating renewable energy sources with the grid, offering vital insights for academics and policymakers. Ultimately, this review emphasizes the need for economical cultivation methods, waste stream utilization, and scalable bioreactor designs, thereby considerably advancing sustainable energy options.